Eprosartan-based hypertension therapy, systolic arterial blood pressure and cognitive function: analysis of Middle East data from the OSCAR study - Radaideh; Choueiry; Eid; Ismail; Berrou J; Sedefdjian; Sévenier; Pathak (Vascular Health and Risk Management, 2011)
Ghazi Ahmad Radaideh1, Patrick Choueiry2, Amr Ismail2, Elie Eid3, Jean-Pascal Berrou4, Armand Sedefdjian5, Frank Sévenier6, Atul Pathak71Rashid Hospital of Dubai, Dubai, United Arab Emirates; 2Abbott Gulf – Levant; 3Division of Cardiology, American University of Beirut, Beirut, Lebanon; 4Abbott Products Operations AG, Allschwill, Switzerland; 5EvidenceBased Communication (EBC), Rueil-Malmaison, France; 6Fovéa Group, Rueil-Malmaison, France; 7Departments of Clinical Pharmacology and Cardiology, Institut National de la Santé et de la Recherche Médicale U1048, Université de Toulouse-UPS, Centre Hospitalier Universitaire de Toulouse, Toulouse, FranceBackground: Studies have indicated a relationship between hypertension and cognitive function. The possible effect of antihypertensive therapy on cognitive disorders is therefore a matter of interest.Materials and methods: The Observational Study on Cognitive function And SBP Reduction (OSCAR) was an open-label, multinational trial designed to evaluate the impact of eprosartan-based antihypertensive therapy on cognitive function in patients with essential hypertension. Eprosartan 600 mg/day for 6 months (with provision for additional medication as needed) was initiated in hypertensive subjects aged ≥50 years. A total of 853 patients in an intention-to-treat cohort from seven countries of the Middle East was identified for subgroup analysis.Results: Arterial blood pressure was reduced significantly (P < 0.001) during the study: At the end of 6 months of eprosartan-based therapy, the mean (±SD) reduction from baseline was 32.1 ± 14.3/14.6.3 ± 8.6 mmHg (P < 0.001). Mean pulse pressure was reduced by 18.3 ± 13.1 mmHg (P < 0.0001 vs baseline). Blood pressure was normalized (systolic <140 mmHg and diastolic <90 mmHg) in 68.2% of patients. The overall mean Mini-Mental State Examination (MMSE) score after 6 months of eprosartan-based therapy was one-point higher than at baseline (P < 0.001). MMSE score on completion of 6 months’ follow-up was either unchanged or increased from baseline in 793 (93%) individuals and decreased in 60 (7%). Factors associated with stability of or improvement in cognitive function included MMSE score at baseline, diastolic blood pressure (DBP) at baseline, and treatment-induced change in DBP.Conclusion: Results from the Middle East subgroup of OSCAR are supportive of the hypothesis that antihypertensive therapy based on angiotensin-receptor blocker therapy with eprosartan may be associated with preservation or improvement of cognitive function.Keywords: hypertension, eprosartan, cognitive function, Middle East